The Correlation between Distance Learning and the Independent Learning among University Students - Ilfi Intansari; Ujang Sugara; Wina Rahayu; Rochelle Diaz Naniong (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine the importance of technological literacy in supporting the independent learning of Elementary School Teacher Education students in the context of distance learning. With the development of information and communication technology, distance learning has become a commonly used method, facilitating access to various learning resources without time and place limitations. However, the implementation of distance learning faces challenges, including limited access to technology, readiness of teaching materials, and limitations in effective communication between lecturers and students. This study uses a quantitative correlational method with a total sampling technique on 44 distance learning students to analyze the relationship between online learning and independent learning. The analysis results show that although digital literacy is important, there is no significant relationship between online learning and student independent learning. This finding indicates the need to improve digital literacy to support optimal independent learning in an online learning environment.